Evidence of Neighborhood Effects from Moving to Opportunity: LATEs of Neighborhood Quality - Aliprantis, Dionissi; Richter, Francisca G.-C. (The Review of Economics and Statistics, 2020)
Abstract This paper estimates neighborhood effects on adult labor market outcomes using the Moving to Opportunity (MTO) housing mobility experiment. We propose and implement a new strategy for identifying transition-specific effects that exploits identification of the unobserved component of a neighborhood choice model. Estimated local average treatment effects (LATEs) are large, result from moves between the first and second deciles of the national distribution of neighborhood quality, and pertain to a subpopulation of nine percent of program participants.